Cultural differences in communication between native and non-native ESL teachers / Nurhezrin Anuar - Nurhezrin , Anuar (2017)
Misunderstandings in intercultural communication may occur because of many factors, one of which can be attributed to differences in cultural communication style and values. Focusing on the narrations of five native and five non-native English teachers, this study aims to understand if misunderstandings occur while they are working in a school setting. A qualitative research in design, this study uses discourse analysis as a framework to analyse data. Specifically, Hofstede’s (1984) Cultural Dimension, Hall’s (1983) High/Low Context Cultures and Ting-Toomey’s (1999) Intercultural Conflict Management Skills were combined as a model to analyse data. Findings suggest that the participants perceived to experience misunderstandings while working together with majority of these misunderstandings being due to a difference in cultural variations in communication styles and values. The findings of this study would benefit researchers, educators, practitioners as well as travellers and in particular those who specialises in intercultural communications. Nonetheless, due to the limitation of the participants involved and the restricted school setting, findings cannot be generalised.